Fate of organic pollutants in soil effect of microbial growth on hydrodynamic properties - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT: A series of experiments was conducted to investigate the hydrodynamic characteristics of orous media in the presence of microbial growth. The study was performed in a laboratory scale column into which retort water (mining liquid waste) labeled with a tritium tracer was continuously fed Three tracer experiments were conducted during the column operation. The results demonstrated that a portion of the feed was transported through macrochannels, the extent of which reduced with time, i.e. it was 50%, 11%, and 5% (of the total feed) after the column was operated for 4 weeks, 12 weeks, and 21 weeks, respectively. The dispersion coefficient, D, was obtained by fitting the tracer data with a one-dimensional convection-dispersion model. The short-circuiting was accounted by assuming that the system consisted of two independent columns, A (short circuit) and B (column). The feed was split between columns A and B. This modification of the convection-dispersion model fitted the tracer data reasonably welt The value of D for column A was 87.6 cm2/h, 80.4 cm2/h, and 15.8 cm2/h and that for column B was 0.55 cm2/h, 1.51 cm2/h, and 7.85 cm2/h, after 4, 12, and 21 weeks of the column operation, respectively.